Analysis of sugarcane herbicides in marine turtle nesting areas and assessment of risk using in vitro toxicity assays. (October 2017) - Allan, Hannah L.; van de Merwe, Jason P.; Finlayson, Kimberly A.; O'Brien, Jake W.; Mueller, Jochen F.; Leusch, Frederic D.L.
Abstract: Agricultural processes are associated with many different herbicides that can contaminate surrounding environments. In Queensland, Australia, herbicides applied to agricultural crops may pose a threat to valuable coastal habitats including nesting beaches for threatened loggerhead turtles ( Caretta caretta ). This study 1) measured concentrations of herbicides in the beach sand of Mon Repos, an important marine turtle nesting beach in Australia that is adjacent to significant sugarcane crops, and 2) investigated the toxicity of these herbicides to marine turtles using a cell-based assay. Samples of sand from turtle nest depth and water from surrounding agricultural drains and wetlands were collected during the wet season when herbicide runoff was expected to be the greatest and turtles were nesting. Samples were extracted using solid phase extraction and extracts were analysed using chemical analysis targeting herbicides, as well as bioanalytical techniques (IPAM-assay and loggerhead turtle skin cell cytotoxicity assay). Twenty herbicides were detected in areas between sugarcane crops and the nesting beach, seven of which were also detected in the sand extracts. Herbicides present in the nearby wetland were also detected in the beach sand, indicating potential contamination of the nesting beach via the river outlet as well as ground water. Although herbicides were detected in nesting sand, bioassays using loggerhead turtle skin cells indicated a low risk of acute toxicity at measured environmental concentrations. Further research should investigate potentially more subtle effects, such as endocrine disruption and mixture effects, to better assess the threat that herbicides pose to this population of marine turtles. Highlights: Herbicides were detected in sand samples taken from turtle nest depths ranging from 60 to 100 cm. In sand, photosystem II inhibiting herbicides were detected in the highest concentrations. Turtle cell bioassays indicated a low risk of acute toxicity at concentrations detected on nesting beaches.